Fostering Religious Character Through The Pancasila Student Profile Strengthening Project at SMA Negeri 1 Nubatukan - Muh. Sulaiman Rifai Aprianus Mukin; Tobroni Tobroni; M. Nurul Humaidi (Pelopor Publikasi Akademika, 2024)
This research focuses on the formation of students' religious character in the midst of globalization and technological advancement, which affects the behavior and moral values of the younger generation. The Pancasila Student Profile Strengthening Project is one of the government's efforts to instill students' religious values that are in line with Pancasila. This study uses a qualitative approach with a case study at SMA Negeri 1 Nubatukan. Data was collected through documentation of related programs, interviews with teachers, students, and principals, and observations. The analysis process was carried out descriptively with the aim of explaining how the concepts, implementation, and impact of this project were carried out and their influence on the formation of students' religious character. The results of the study show that the program can improve students' understanding of Pancasila religious values while maintaining the diversity of religions and beliefs of students at Nubatukan State High School. These changes show that students are developing academically and emotionally as well as socially. However, there are several problems that arise today, such as lack of parental involvement, limited resources, limited time, mismatch of interests and characteristics of students, and rapid curriculum changes. This research finds that through the Pancasila Student Profile Strengthening Project, schools, parents, and the community must work together to support the development of religious character. In addition, it is necessary to improve facilities and teacher training related to this program so that character development is more sustainable and effective.